Effects of strain, nutrients concentration and inoculum size on microalgae culture for bioenergy from post hydrothermal liquefaction wastewater - Li, Zhang; Haifeng, Lu; Zhang, Yuanhui; Shanshan, Ma; Baoming, Li; Zhidan, Liu; Na, Duan; Minsheng, Liu; Buchun, Si; Jianwen, Lu (International Journal of Agricultural and Biological Engineering, 2017)
Cultivating microalgae in post hydrothermal liquefaction wastewater (PHWW) offers many benefits, including nutrients recovery and reuse, wastewater purification and biomass production. However, the high nutrients concentration and toxic substances in PHWW undermine the efficiency of biomass production and nutrient recovery. This study aimed to investigate the effects of the microalgae strains, initial nutrients concentrations and inoculum sizes on biomass production and nutrient recovery using PHWW as the cultivation medium. Results indicated that both biomass production and nutrients recovery were successfully improved by using the screened microalgae strain at the desirable initial nutrient concentration with the suggested algae inoculum size. Chlorella vulgaris 1067 probably demonstrated the strongest tolerance ability among the five microalgae strains screened, and performed well in the diluted PHWW, of which initial TN concentration was approximately 500 mg/L. The desirable inoculum size was determined to be 0.103-0.135 g/L. The biomass daily productivity was increased by 15.67-fold (reached 0.13 g/(L·d)). With the above optimal conditions, high biomass production and nutrient recovery from the PHWW to produce microalgae biomass for bioenergy production were achieved.Keywords: post hydrothermal liquefaction wastewater, microalgae strain screening, inoculum size, initial nutrient concentration, nutrient recovery, biomass productionDOI: 10.3965/j.ijabe.20171002.2882Citation: Zhang L, Lu H F, Y H Zhang, Ma S S, Li B M, Liu Z D, et al. Effects of strain, nutrients concentration and inoculum size on microalgae culture for bioenergy from post hydrothermal liquefaction wastewater. Int J Agric & Biol Eng, 2017; 10(2): 194–204.